Synthesis, biological evaluation and molecular modelling of diversely functionalized heterocyclic derivatives as inhibitors of acetylcholinesterase/butyrylcholinesterase and modulators of Ca2+ channels and nicotinic receptors - Marco, JL (2015)
The synthesis and the biological activity of compounds 5-40 as inhibitors of acetyleholinesterase (AChE) and butyrylcholinesterase (BuChE), as well as modulators of voltage-dependent Ca2+ channels and nicotinic receptors, are described. These molecules are tacrine analogues, which have been prepared from polyfunctionalized 6-amino-5-cyano-4H-pyrans, 6-amino-5-cyano-pyridines and 5-amino-2-aryl-3-cyano-1,3-oxazoles via Friedlander reaction with selected cycloalkanones. These compounds are moderate acetylcholinesterase and butyrylcholinesterase inhibitors, the BuChE/AChE selectivity of the most active molecules ranges from 10.0 (compound 29) to 76.9 (compound 16). Interestingly, the 'oxazolo-tacrine' derivatives are devoid of any activity. All compounds showed an important inhibitory effect on the nicotinic acetylcholine receptor. Most of them also blocked L-type Ca2+ channels, and three of them, 64, 19 and 67, the non-L type of Ca2+ channels. Molecular modelling studies suggest that these compounds might bind at the peripheral binding site of AChE, which opens the possibility to design inhibitors able to bind at both, the catalytic and peripheral binding sites of the enzyme. (C) 2004 Elsevier Ltd. All rights reserved.